Danish guidelines for treating acute colonic obstruction caused by colorectal cancer—a review - Mikalonis, Martynas; Avlund, Tue Højslev; Løve, Uffe Schou (Frontiers in Surgery, 2024)
Acute onset of colonic obstruction caused by colorectal cancer occurs in approximately 14% of Danish patients with colon cancer(1). Given that colorectal cancer is a common cancer with about 4,500 new cases annually, acute onset will occur in a reasonably large number of patients in Danish emergency departments, and all surgeons should be familiar with the treatment principles. A revised guideline from the Danish Colorectal Cancer Group is currently underway, and this status article reviews the latest knowledge and recommendations.